Antagonistic activity of terrestrial Streptomyces sp. VITNK9 against Gram negative bacterial pathogens affecting the fish and shellfish in aquaculture - Ishaque Nabila, Mohammed; Kannabiran, Krishnan (Revista de Biología Marina y Oceanografía, 2018)
A total of 72 morphologically different actinomycetes isolates were isolated from samples collected at different regions of Vellore, Tamil Nadu, India and screened for its antibacterial activity against fish and shellfish pathogens. All actinomycetes isolates were screened for antibacterial activity by cross streak method against the selected fish and shellfish bacterial pathogens including Aeromonas caviae, Aeromonas hydroplila, Edwardsiella tarda, Vibrio anguillarum and Vibrio harveyi. Secondary screening of antagonistic isolates by well diffusion method leads to the identification of potential isolate. Culture conditions for the potential isolate were optimized for maximal growth and yield of the ethyl acetate (EA) crude extract. The potential isolate was characterized by molecular taxonomy and phylogeny and identified as Streptomyces species and named as Streptomyces sp. VITNK9. The 16S rDNA nucleotide sequence was searched through the GenBank database and showed 83% similarity to Streptomyces vinaceusdrappus. The EA extract prepared from Streptomyces sp. VITNK9 showed moderate antagonistic activity accessed by the formation of zone of growth inhibition against, Aeromonas caviae (15.33 mm), Aeromonas hydrophila (17.66 mm), Edwardsiella tarda (18.33 mm), Vibrio anguillarum (14.33 mm) and Vibrio harveyi (14.33 mm). The MIC value of EA extract was ranged between 0.03-0.125 mg mL-1. The GC-MS spectrum of the ethyl acetate extract revealed the presence of two major compounds, pyrrolo [1,2-A] pyrazine-1,4-Dione (56.67%) and Hexahydro-3-(2-Methylpropyl) (27.91%), respectively. The results of the study suggest that Streptomyces sp. VITNK9 is a potential source for antagonistic secondary metabolites against fish and shellfish bacterial pathogens.